(3GdeMUd TQM GdeaUd ddReNTQis - (3YHO Gddg Hf GdMSjf Hf YHO Gddg GdYcHQj GdHZOGOj, CHh GdHbGA, eMH GdOjf,J (B616 (3g` s; (3eMehO Hf YeQ Hf eMeO Hf CMeO GdNhGQRej GdReNTQqj, LGQ Gddg, CHh GdbGSe,(B538 (3g`s
(3ChdgG (B:s
(3JHJOF Hbhdg(B: (3bdJ efge ef bGd jhSa HeKdg hHLejY GdeVGaGJ aCLGR eQQJ HGdQLd UGMHc hUGMH RjO bHd GdcdGe Ydi GdeHge s
(3BNQgG (B:s
(3jfJgi HaUd cja LGR eLQi GdXQha heYfGg GdSDGd Yf GdMGd s
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B178 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B12 - (3U (B186 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B2 - (3U (B402s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B17 - (3U (B395 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1774s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdfMhs